FORMULATION OF LOTION OF GERGA ORANGE PEEL ETHANOL EXTRACT WITH VARIATION OF EXTRACT CONCENTRATION - Krisyanella Krisyanella; Resva Meinisasti; Silvi Elvianita (Proceeding B-ICON, 2022)
Gerga Orange (Citrus nobilis L. Var. RGL) are the main commodity in Lebong Regency, Bengkulu Province. These oranges have been processed by the community into syrup preparations and from this activity produce waste in the form of fruit peels. Based on previous research, the peel of this citrus fruit is known to have antioxidant and antibacterial activity, so it can be used as a raw material in the manufacture of lotion preparations. The purpose of this study was to determine the characteristics of the three lotion formulations from the ethanolic extract of the gerga orange peel (Citrus nobilis L. Var. RGL) with various concentrations of 8% (F1), 10% (F2), 12% (F3). The method used is the experimental method. The results showed that the three formulations of lotion met the standard of good lotion. In the organoleptic test, there were differences in the color of the preparation, where the color became more concentrated as the concentration of the extract increased. In the homogeneity test, the three formulas showed good homogeneity until the 14th day of testing. The pH of the three formulas was also in accordance with the SNI 16-4399-1996 standard, namely 4.5-8. The three formulas also did not cause allergic reactions to 10 respondents. Based on the results of the research that has been done, it can be concluded that all formulas of the ethanol extract of the gerga orange peel (Citrus nobilis L. Var. RGL) with varying concentrations can be formulated as lotion preparations that are physically and organoleptically stable, as well as the standard of SNI 16-4399-1996 in terms of pH of the preparation and irritation test. Of the three formulas, formula 1 has an advantage over the other formulas because it has a less intense color, which makes it superior in appearance.